THE IMPLEMENTATION OF SCHOOL OPERATIONAL ASSISTANCE AT THE BORDER - Abao, Antonia Sasap; Gaffar, Zakiah Hasan (Jurnal Sosial Humaniora, 2022)
The government has made various efforts to increase school participation rates such as through the provision of School Operational Assistance (BOS) which has been operating since 2005. However, in 2019 it was noted that many of the population of Suruh Tembawang Village were illiterate and did not graduate from Elementary School. Therefore, this study was conducted to describe the implementation of the BOS in two schools in Suruh Tembawang Village. This research used the descriptive method with a qualitative approach. The results showed that part of the BOS funds in the schools of Suruh Tembawang have been used in accordance with the provisions stipulated in Permendikbud Number 1 of 2018. However, expenditure of the BOS funds on infrastructure and maintenance had not been properly observed. In terms of teaching staff and administrations, many teachers, including the school principals were often unavailable on site. The community members interviewed expressed their disappointment in the implementation of the BOS funds, particularly on how the school administration used the funds for the operation of the schools. This was the result of a lack of community engagement, a lack of supervision, and a lack of transparency. In order to maximize the use of BOS funds in both schools, the schools must involve the school committee and its members, village officials, parents of students in planning, budgeting, and managing the BOS funds.